SISTEM TRANSAKSI E-COMMERCE DALAM PERSPEKTIF KUH PERDATA DAN HUKUM ISLAM - Santoso, Sugeng (IAIN Tulungagung, 2016)
Trading transactions are not only done conventionally, where buyersand sellers meet face to face. Now the transaction has been switchedinto cyber-spaced transaction, where the trading transactions areconducted through social networking, computers, mobile phones,etc. Such Transactions are called online trading transactions(e-commerce). According to Islamic law e â commerce transactionshould also meet some required conditions such as employers in onlinecommerce (e-commerce) are qualified to be taxable income. But ifthe income tax law that is used in the taxation for online commercetransactions (e-commerce) is employed, the tax will not be able tobe maximized because basically e-commerce transactions are verydifferent from conventional trading transactions. So the need for newrules to serve as a legal basis of the taxation of income in e-commercetransactions is emerging.Kata kunci: Sistem Transaksi, E-Commerce, KUH Perdata, HukumIslam